RANCANG BANGUN SISTEM INVENTORY LABORATORIUM KOMPUTER DENGAN METODE END USER DEVELOPMENT (STUDI KASUS: SMK BINAKARYA MANDIRI) - Sekar Wulandari; Budi; Amelia Sabila Qolby; Mami Maryati (Jurnal Teknologi Informasi dan Digital, 2025)
The management of computer laboratory inventory at SMK Binakarya Mandiri was previously conducted manually, making it prone to recording errors, slow in report generation, and unable to monitor stock in real-time. This research aims to design and build a web-based inventory information system using the End User Development method to improve efficiency, accuracy, and ease of inventory management. The system was developed using PHP Native programming language and MySQL database, with main features including item data recording, stock monitoring, borrowing and item damage records, as well as report generation in PDF format. Testing was conducted using the Black Box Testing method to ensure all functions operate according to requirements. The research results show that the system successfully meets the inventory management needs in the computer laboratory, provides accurate reports, and facilitates the recording and monitoring process of items in real-time.